2011
DOI: 10.1200/jco.2011.29.15_suppl.3503
|View full text |Cite
|
Sign up to set email alerts
|

The impact of capecitabine and oxaliplatin in the preoperative multimodality treatment in patients with carcinoma of the rectum: NSABP R-04.

Abstract: Lymph node ratio risk classification in stage III colon cancer: A pooled analysis of 16,425 patients from the ACCENT database.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
90
1
15

Year Published

2013
2013
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(107 citation statements)
references
References 0 publications
1
90
1
15
Order By: Relevance
“…Based on these encouraging results, several trials were carried out to determine the benefits of oxaliplatin in addition to standard fluopyridinaminebased regimens in rectal cancer (ACCORD12/0405Prodige, CAO/ARO/AIO04, ADORE, STAR01, NSAPB R04, PETACC6) [7378] . While some studies reported significant improvement in pathological response and diseasefree survival [76,78] , others found no superiority of oxaliplatin, but instead an increased risk of acute toxicity [74,75,77,79] . Only four trials reported the data on survival.…”
Section: Oxaliplatin-based Regimensmentioning
confidence: 99%
“…Based on these encouraging results, several trials were carried out to determine the benefits of oxaliplatin in addition to standard fluopyridinaminebased regimens in rectal cancer (ACCORD12/0405Prodige, CAO/ARO/AIO04, ADORE, STAR01, NSAPB R04, PETACC6) [7378] . While some studies reported significant improvement in pathological response and diseasefree survival [76,78] , others found no superiority of oxaliplatin, but instead an increased risk of acute toxicity [74,75,77,79] . Only four trials reported the data on survival.…”
Section: Oxaliplatin-based Regimensmentioning
confidence: 99%
“…Oxaliplatin chemotherapy during radiotherapy was tested in several clinical trials. Four phase III clinical trials added weekly Oxaliplatin (50 or 60 mg/m2) in one arm of radiotherapy plus concurrent 5FU or Capecitabine (STAR-01 [5], ACCORD12/0405 Prodige 2 [15], NSABP R-04 [16], CAO/ ARO/AIO-04 [17]). …”
Section: Discussionmentioning
confidence: 99%
“…Было проведено сравнение групп с ФУ против капецитабина и групп с оксалиплати-ном против режимов без оксалиплатина. Было показано, что эффективность капецитабина была эквивалентна длительной инфузии ФУ: частота pCR составила 22,2 % и 18,8 % соот-ветственно (р=0.12), сфинктеросохранные операции выполнены 62,7 % и 61,2 % больных (р=0.59), стадия уменьшилась в 23,0 % и 20,7 % случаев (р=0.62) при сравнимой токсичности: диарея 3 / 4 степени регистрировалась в 10,8 % и 11,2 % наблюдений [23]. Преимуществом ка-пецитабина при этом является его пероральная форма и возможность избежать использования центрального венозного катетера.…”
Section: рак прямой кишки (рпк)unclassified